1998
DOI: 10.1126/science.281.5377.692
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Transcription Factor Network Required for Differentiation and Metabolism

Abstract: Hepatocyte nuclear factors (HNFs) are a heterogeneous class of evolutionarily conserved transcription factors that are required for cellular differentiation and metabolism. Mutations in HNF-1alphaand HNF-4alpha genes impair insulin secretion and cause type 2 diabetes. Regulation of HNF-4/HNF-1 expression by HNF-3alpha and HNF-3beta was studied in embryoid bodies in which one or both HNF-3alpha or HNF-3beta alleles were inactivated. HNF-3beta positively regulated the expression of HNF-4alpha/HNF-1alpha and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
241
4
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 321 publications
(259 citation statements)
references
References 24 publications
10
241
4
4
Order By: Relevance
“…This is due either to functional redundancy between individual FoxA and GATA factor proteins or an essential role for some of these factors prior to the onset of hepatic development. [61][62][63][64][65][66][67][68][69][70] For example, development of Gata6 Ϫ/Ϫ mouse embryos is blocked before hepatic specification due to an indispensable requirement for GATA6 in extraembryonic endoderm differentiation. 63,65 This early embryonic lethality has, however, recently been circumvented by providing Gata6 Ϫ/Ϫ embryos with a wild-type extra-embryonic endoderm via tetraploid embryo complementation.…”
Section: From Where Do Hepatic Cells Arise?mentioning
confidence: 99%
“…This is due either to functional redundancy between individual FoxA and GATA factor proteins or an essential role for some of these factors prior to the onset of hepatic development. [61][62][63][64][65][66][67][68][69][70] For example, development of Gata6 Ϫ/Ϫ mouse embryos is blocked before hepatic specification due to an indispensable requirement for GATA6 in extraembryonic endoderm differentiation. 63,65 This early embryonic lethality has, however, recently been circumvented by providing Gata6 Ϫ/Ϫ embryos with a wild-type extra-embryonic endoderm via tetraploid embryo complementation.…”
Section: From Where Do Hepatic Cells Arise?mentioning
confidence: 99%
“…Of these, HNF-3b has been shown to be involved in beta-cell-specific transcription of the IPF1 gene [7]. Characterization of HNF-3b zero embryonic stem cells has suggested that HNF-3b positively regulates the HNF-4a/HNF-1a genes and their downstream target genes [8]. Thus, the molecular defects of HNF-3b or accessory factors in the functional complex could cause a decrease in synthesis of IPF1 and HNF-4a/ HNF-1a.…”
mentioning
confidence: 99%
“…Indeed, in animals, the visceral endoderm produces a number of proteins such as, for instance, alpha foetoprotein, transthyretin, apolipoproteins and glucose transporters which are also found in the outer cell layer of the EBs [27]. In addition, tissuespecific transcriptional regulators of these genes in the visceral endoderm are functional in the outer layer of EBs [28,29]. Insulin is also expressed in the yolk sac visceral endoderm [30], which is consistent with our present observation that insulin is produced by the outer cell layer of EBs.…”
Section: Discussionmentioning
confidence: 99%